EDUCAÇÃO AMBIENTAL, DESENVOLVENDO ATIVIDADES PARA MINIMIZAR O RUÍDO NA ESCOLA - Lourenço, Giane Margarete Scarpatto; Silveira, Djalma Dias da (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2011)
A major problem faced by the population, is the lack of sanitation and care for water and soil,especially in rural areas, where there is no specific type of control over the issues of environmentalsanitation or when there is done so unsystematic, only appears to be triggered when a healthproblem in the community. Water pollution and soil increases every day due to residues of organicand inorganic materials, due to lack of sanitation and care of the man himself with hisenvironment, and also daily activities of rural workers that may be irreversible environment. Thisstudy aimed to relate human activities with environmental problems in the interior of Santo Angelo - RS, focusing on the pollution of soil and water. For this reason, participants are doingwork environment perception survey data on key factors of contamination in rural areas, througha photographic survey questionnaire and socio-environmental. From these data we can verify thequality of life in relation to issues of environmental sanitation and awareness of the population,allowing for discussion and promotion of environmental education, encouraging the formation ofa sense of citizenship and helping to promote sanitation in these areas, forming citizens able tocharge their rights to practice their duties to the preservation of natural resources, especiallywater and soil.